Efectos del tratamiento de ortodoncia en la imagen del cuerpo y en la autoestima de los adolescentes. Informe final (2005)
ABSTRACT: This research project consisted of two steps; the purpose of the first one was to find out the reasons adolescents had for orthodontic consultation and their expectations on the corresponding treatment concerning their body image and self-esteem. In the second step, once treatment was over, the work focused on interpreting the effects of treatment on such self-image and self-esteem. Once treatment had finished, our findings corroborated that a demand about image underlies the request of adolescents for intervention on their organisms. Besides, it was found that adolescents experienced a transient increase in self-esteem; this effect was not long-lasting because the transformation of their organism did not solve their fundamental uneasiness with their body and with themselves.